Bumble-ardy - Sendak, Maurice (New York : Harper Collins, 2011)
Bumble-ardy, a mischievous pig who has never had a birthday party, invites all his friends to a masquerade that quickly gets out of hand.
"Michael di Capua books"--T.p. verso.
Booklist
Publisher's Weekly
School Library Journal starred
Booklist, July 2011
Horn Book, September 2011
Keywords: Birthdays -- Juvenile fiction; Parties -- Juvenile fiction; Swine -- Juvenile fiction; Birthdays -- Fiction; Parties -- Fiction; Pigs -- Fiction; Birthdays -- Fiction; Parties -- Fiction; Pigs -- Fiction; Picture books for children